2003
DOI: 10.1104/pp.103.026039
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Anthocyanin Biosynthesis inGerbera hybrida(Asteraceae) Suggests Conserved Protein-Protein and Protein-Promoter Interactions between the Anciently Diverged Monocots and Eudicots

Abstract: We have identified an R2R3-type MYB factor, GMYB10, from Gerbera hybrida (Asteraceae) that shares high sequence homology to and is phylogenetically grouped together with the previously characterized regulators of anthocyanin pigmentation in petunia (Petunia hybrida) and Arabidopsis. GMYB10 is able to induce anthocyanin pigmentation in transgenic tobacco (Nicotiana tabacum), especially in vegetative parts and anthers. In G. hybrida, GMYB10 is involved in activation of anthocyanin biosynthesis in leaves, floral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 60 publications
3
104
0
Order By: Relevance
“…In situ hybridization analysis using full-length GhCYC2 probe was performed as in ref. 39, with the following exceptions: probe concentration was 0.7 g/ml/kb and detection time was 40 -45 h. SEM analysis of the Gerbera flower primordia was performed as described in ref. 5.…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization analysis using full-length GhCYC2 probe was performed as in ref. 39, with the following exceptions: probe concentration was 0.7 g/ml/kb and detection time was 40 -45 h. SEM analysis of the Gerbera flower primordia was performed as described in ref. 5.…”
Section: Methodsmentioning
confidence: 99%
“…They also served as marker genes in studies of inflorescence development since pigmentation patterns in various gerbera varieties are strictly correlated with the anatomy of the complex inflorescence (Helariutta et al 1995b). More recent studies have identified a number of regulatory genes that are required for organ and tissue specific activation of biosynthetic genes and anthocyanin pigmentation (Elomaa et al , 2003. These studies have provided intrinsic scientific information about transcriptional regulation of gene expression in plants.…”
Section: Biotechnology In Horticultural Speciesmentioning
confidence: 99%
“…In1 is a negative regulator of anthocyanin synthesis, which gives an intense purple color when mutated, whereas Rc is a positive regulator of proanthocyanidin synthesis, which has no color when the function is lost (Burr et al, 1996). All of the other genes on the tree whose functions have been established are positive regulators, suggesting that the ancestral function is positive regulation (Goff et al, 1992;Nesi et al, 2000;Spelt et al, 2000;Sakamoto et al, 2001;Bernhardt et al, 2003;Elomaa et al, 2003).…”
Section: Phylogenetic Comparisonmentioning
confidence: 99%